Sociodemographic Impact and Acquaintance on Antibiotic Resistance Among Outpatients in Specialist Hospital, Malaysia - Jayasingh Chellammal, Hanish Singh; Manan, Mohamed Mansor; Kupusamy, Thayashini; Ming, Long Chiau; Mohd Faizal, Shafeeq (IIUM Medical Journal Malaysia, 2021)
INTRODUCTION: Awareness on antibiotics resistance among outpatients in hospital settings is reasonably explored and this study aimed to investigate the sociodemographic impact and the level of acquaintance towards antibiotics practice and resistance. MATERIALS AND METHODS: This cross-sectional study was conducted on 270 patients from the outpatient department of KPJ Seremban Specialist Hospital (KPJSSH), Malaysia. A pre-validated questionnaire was used to collect the data on the demographics of the patients, their knowledge, attitude, and usage of antibiotics. The study was approved by the KPJUC ethics committee (KPJUC/RMC/BPH/EC/2017/104). RESULTS: The mean age of the respondents was 36 ± 11.07 years and 50.37% of them have moderate knowledge on antibiotics. The knowledge and attitude on antibiotics usage exhibited a significant difference (p=0.001) amongst these patients in association with literacy. The results showed that the literate respondents have significant knowledge on the identification of antibiotics (p=0.021), their roles, and adverse effects (p=0.004). The attitude of the respondents towards following the prescription was significantly associated with their literacy (p=0.004). CONCLUSION: This study reveals that respondents have the least knowledge on antibiotic course compliance and termination of therapy, which could lead to antimicrobial resistance. In conclusion, inculcating the knowledge of antimicrobial resistance, adverse effects, and course compliance among the patients may help overcome the national and global issues on multi-drug-resistant diseases.